Surface plasmon enhanced the responsivity of the ZnO/Pt nanoparticles/ZnO sandwich structured photodetector via optimizing the thickness of the top ZnO layer. (October 2016) - Guo, Zexuan; Jiang, Dayong; Zhao, Man; Guo, Fei; Pei, Jianan; Liu, Rusheng; Sun, Long; Hu, Nan; Zhang, Guoyu
Graphical abstract: Highlights: UV photodetector based on the ZnO/Pt NPs/ZnO films by magnetron sputtering method. By optimizing its thickness, highly efficient enhanced UV photodetector is achieved. This is ascribed to the surface plasmon of Pt NPs. Abstract: Based on the ZnO/Pt nanoparticles/ZnO multilayer films by magnetron sputtering method, we elaborate the ultraviolet (UV) photodetectors and deduce that they provide an ideal platform for highly using efficient surface plasmon (SP) modes. By only adjusting the thickness of the top layer and remaining other conditions unchanged, we draw a conclusion that the responsivity of the sandwich photodetector can be drastically increased from 0.08 to 0.40 A/W. It firmly provides for our findings that the responsivity enhancement factors without Pt nanoparticles (NPs) are apparently smaller than those by means of introducing Pt NPs. This can be ascribed to the SP of Pt NPs. The near-field effect of SP results in the dependence of the responsivity enhancement of ZnO films on the top layer film thickness. Which are in good agreement with theoretical calculations.